Answer:
(D) -k2 + k - 13
Step-by-step explanation:
Pulling out like terms :
2.1 Pull out like factors :
-k2 + k - 13 = -1 • (k2 - k + 13)
Trying to factor by splitting the middle term
2.2 Factoring k2 - k + 13
The first term is, k2 its coefficient is 1 .
The middle term is, -k its coefficient is -1 .
The last term, "the constant", is +13
Step-1 : Multiply the coefficient of the first term by the constant 1 • 13 = 13
Step-2 : Find two factors of 13 whose sum equals the coefficient of the middle term, which is -1 .
-13 + -1 = -14
-1 + -13 = -14
1 + 13 = 14
13 + 1 = 14
Observation : No two such factors can be found !!
Conclusion : Trinomial can not be factored
Final result :
-k2 + k - 13
Processing ends successfully
plz mark me as brainliest :)
Answer:
equal to
Step-by-step explanation:
Answer:
-3, -4, -5, -6, -7, -8
Step-by-step explanation:
Im not sure if that is what you are looking for or if you want x ≤ -3 and x ≥ -8
Y=3.5x
Pts are (1,3.5),(2,7),(3,10.5)
Answer:
The answer is C
Step-by-step explanation:
Reflecting across the y-axis is like folding across the y-axis.
2,-2, turns into -2,-2
Hope this helped!